Economics of public elementary education some institutional findings - Malaya, J. Eduardo E.; Malaya, Corazon Enciso
This study reached some conclusions which are rather of common knowledge among teachers in the field (e.g., the sore lack of textbooks and other instructional supplies) and others which are admittedly prone to controversy, notably the absence of economies of scale. Indeed, if there is any sector, where cost-saving/result maximizing measures are sorely needed, education is one of them.
Keywords: Education, Elementary -- Economic aspects -- Philippines; Education, Elementary -- Philippines -- Finance; Education and state -- Philippines